Tarekat Naqsabandiyah dan Pembangunan Karakter Bangsa dalam Masyarakat Jawa - A. Ainul Yaqin; Badrun Badrun (Medan Resource Center, 2022)
The development of the teachings of Sufism in Java contained in the Naqsabandiyah Order movement has continued to increase. This development was marked by the presence of several figures who gave influence through the fusion of the Naqsabandiyah Order with other orders. As a religious movement that is always considered to be concerned with exclusive spiritual issues, this article aims to include (1) to find out the history and concepts of the Naqsabandiyah Order in Java, (2) to find out the forms of Islam in the Naqsabdiyah Order in building the nation's character in Javanese society. This article is a literature survey that uses historical research methods, including: heuristic, verification, interpretation and historiography.